2015
DOI: 10.1186/s12952-015-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Case-control association between CCT-associated variants and keratoconus in a Saudi Arabian population

Abstract: BackgroundKeratoconus (KC) is the most common primary ectatic disease of the cornea and a major indication for corneal transplant. To date, limited KC-associated-risk loci have been identified. Association has recently been suggested between KC and 8 single nucleotide polymorphisms (SNPs) in the genomic regions of FNDC3B, COL4A3, MPDZ-NF1B, RXRA-COL5A1, LCN12-PTGDS, FOXO1, and BANP-ZNF469. These SNPs are associated with central corneal thickness (CCT), a known risk factor to KC. We are questioning whether thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Genes coding for collagens COL4A3 (type IV collagen alpha3, COL4A4 (type IV collagen alpha4) have been suggested as well [ 123 , 124 ]; however, additional studies in multiple populations found no association with these SNPs [ 91 , 125 ] or found evidence of their extensive presence in the normal population [ 126 ].…”
Section: Other Potentially Involved Genesmentioning
confidence: 99%
“…Genes coding for collagens COL4A3 (type IV collagen alpha3, COL4A4 (type IV collagen alpha4) have been suggested as well [ 123 , 124 ]; however, additional studies in multiple populations found no association with these SNPs [ 91 , 125 ] or found evidence of their extensive presence in the normal population [ 126 ].…”
Section: Other Potentially Involved Genesmentioning
confidence: 99%
“…In a Han Chinese cohort of 210 patients and 191 controls in northern China, the association was p = 0.005, OR = 3.1 [115]. However, no association was found in a Saudi Arabia study of 108 patients and 300 controls [116]. In contrast, very high risk of rs1324183 to keratoconus, P = 4.30 × 10 −4 OR = 2.22 was shown after genotyping of 133 patients and 367 controls who are Han Chinese in Hong Kong in southern China [117].…”
Section: Mpdz-nf1bmentioning
confidence: 89%
“…Such condition is developed during [10] About this corneal vascularization in 22.22% (n=4) of the cases, it is a factor that should be considered to be one of the complications of DALK due to surface and suture changes. Thus, a history of anterior vascular keratoplasty could represent a triggering factor for corneal opacification [11].…”
Section: Discussionmentioning
confidence: 99%